KEPENTINGAN EKONOMI PERTANIAN DARI PERSPEKTIF ISLAM DAN AMALANNYA DI KALANGAN PESAWAH PADI DI SELANGOR - Ab Rahman, Asmak (Jurnal Syariah, 2019)
Islam encourages agriculture based on the fact that it is one of economic sources of economic development of a state. Islam also connotes the importance of agriculture in the time of Adam. Yusuf Musa and Muhammad peace been upon them. Agriculture plays not only as a revenue of economic development but also it gives a very significant role in muslim worship towards Allah. The example of this can be shown in the fact that, by producing ugric11ltural products, Muslims can perform many other ibadah sunnah such as 'aqiqah, qurban, sadaqah or paying penalty such as fidyah, paying dam and kifarah whirh are mechanisme of wealth redistribution and to ensure food security among poors and needy. A study has been done in Selangor to observe the practice of perfoming tithe, zakah fitr, 'aqiqah. qurban, sadaqah and penalty such as fidyah, paying dam and kifarah among paddy farmers. The finding of the study shows that all of the respondents pay tithe and zakah fitr but for 'aqiqah, qurban, sadaqah and penalty such us fidyah, paying dam and kifarah some of the respondents do not practice them.